Foliar application of various biostimulants produces contrasting response on yield, essential oil and chemical properties of organically grown sage (Salvia officinalis L.) - Farruggia, Davide; Di Miceli, Giuseppe; Licata, Mario; Leto, Claudio; Salamone, Francesco; Novak, Johannes (Frontiers in Plant Science, 2024)
Sage (Salvia officinalis L.) is a medicinal and aromatic plant (MAP) belonging to the Lamiaceae family. Its morphological, productive and chemical characteristics are affected by abiotic and biotic factors. The use of biostimulants seems to be one of the most interesting innovative practices due to fact they can represent a promising approach for achieving sustainable and organic agriculture. Despite a large application in horticulture, the use of biostimulants on MAPs has been poorly investigated. On this basis, a field experiment in a 2-year study was done to assess the effect of foliar treatments with different types of biostimulants (containing seaweeds, fulvic acids and protein hydrolysates) and two frequencies of application on morphological, productive, and chemical characteristics of S. officinalis grown organically in Mediterranean environment. Morphological, productive, and chemical parameters were affected by the factors. The biostimulant application generated higher plant height, chlorophyll content, relative water content, biomass yield and essential oil yield compared to control plants. In addition, more frequent application of biostimulants produced higher biomass and essential oil yield. The application of fulvic acid and protein hydrolysates every week produced the highest total fresh yields (between 3.9 and 8.7 t ha-1) and total dry yields (between 1.3 and 2.5 t ha-1). The essential oil yield almost doubled (33.9 kg ha-1) with a higher frequency of protein hydrolysates application. In this study, 44 essential oil compounds were identified, and the frequency factor significantly influenced the percentage of 38 compounds. The highest percentage of some of the most representative monoterpenes, such as 1,8-cineole, α-thujone and camphor, were observed in biostimulated plants, with average increases between 6% and 35% compared to control plants. The highest values for total phenolics, rosmarinic acid, antioxidant activity were obtained in control plants and with a lower frequency of biostimulant applications. This study emphasizes how biostimulant applications may be used to improve sage production performance and essential oil parameters when produced in agricultural organic system. At the same time, biostimulants application caused a decrease in total phenolic, antioxidant activity and rosmarinic acid values.